Acute hyperammonemic encephalopathy after fluoropyrimidine-based chemotherapy: A case series and review of the literature. Issue 22 (June 2017) - Mitani, Seiichiro; Kadowaki, Shigenori; Komori, Azusa; Sugiyama, Keiji; Narita, Yukiya; Taniguchi, Hiroya; Ura, Takashi; Ando, Masashi; Sato, Yozo; Yamaura, Hidekazu; Inaba, Yoshitaka; Ishihara, Makoto; et al.
Abstract : Abstract: Acute hyperammonemic encephalopathy induced by fluoropyrimidines (FPs) is a rare complication. Its pathophysiology remains unclear, especially given the currently used regimens, including intermediate-doses of 5-fluorouracil (5-FU) or oral FP agents. We aimed to characterize the clinical manifestations in cancer patients who developed hyperammonemic encephalopathy after receiving FP-based chemotherapy. We retrospectively reviewed 1786 patients with gastrointestinal or primary-unknown cancer who received FP-based regimens between 2007 and 2012. Eleven patients (0.6%) developed acute hyperammonemic encephalopathy. The incidence according to the administered anticancer drugs were as follows: 5-FU (8 of 1176, 0.7%), S-1 (1 of 679, 0.1%), capecitabine (2 of 225, 0.9%), and tegafur-uracil (UFT) (0 of 39, 0%). Ten patients (90.9%) had at least 1 aggravating factor, including infection, dehydration, constipation, renal dysfunction, and muscle loss. All the 10 patients met the definition of sarcopenia. Median time to the onset of hyperammonemic encephalopathy in the cycle was 3 days (range: 2–21). Three patients (27.3%) developed encephalopathy during the first cycle of the regimen and the remaining 8 patients during the second or more cycles. Seven patients (63.6%) had received at least 1 other FP-containing regimen before without episodes of encephalopathy. All patients recovered soon after immediate discontinuation of chemotherapy and supportive therapies, such as hydration, infusion of branched-chain amino acids, and oral lactulose intake, with a median time to recovery of 2 days (range: <1–7). Four patients (36.4%) received FP-based regimens after improvement of symptoms; 3 patients were successfully managed with dose reduction, and 1 patient, who had developed encephalopathy due to S-1 monotherapy, received modified FOLFOX-6 therapy without encephalopathy later. FP-associated acute hyperammonemic encephalopathy is extremely rare, but a possible event at any time and even during the administration of oral FP agents. Particular attention is warranted when giving FP-based therapy for patients with aggravating factors, such as sarcopenia. This complication can be properly managed with early detection.